Gasparyan Method of Total Autologous Reconstruction of the Aortic Valve - Gasparyan,Vahe (2020)
Abstract In this case report, I describe a new technique for total reconstruction of the aortic valve with autologous pericardium. The parameters of the cusps were calculated using very simple formulas after measurement of the aortic root intercommissural distances. Glutaraldehyde-treated pericardium was trimmed along the marked line, leaving 2 mm of tissue along the fibrous annulus attachment margin for the suture and small wings on both commissural margins to secure the commissural coaptation between right and noncoronary cusps. The annular margin of each pericardial cusp was sutured to the corresponding fibrous annulus with running 4/0 polypropylene suture. The commissures of pericardial patch and the commissural coaptation between right and noncoronary cusps were secured with mattress 4/0 polypropylene sutures. The coaptation of the three cusps was checked with negative pressure on the left ventricular vent before closure of the aortotomy. Intraoperative transesophageal echocardiogram revealed a peak pressure gradient of 10 mmHg and trivial aortic regurgitation.